G Protein-Coupled Receptors in Osteoarthritis - Wang, Fanhua; Liu, Mingyao; Wang, Ning; Luo, Jian (Frontiers in Endocrinology, 2022)
Osteoarthritis (OA) is the most common chronic joint disease characterized, for which there are no available therapies being able to modify the progression of OA and prevent long-term disability. Critical roles of G-protein coupled receptors (GPCRs) have been established in OA cartilage degeneration, subchondral bone sclerosis and chronic pain. In this review, we describe the pathophysiological processes targeted by GPCRs in OA, along with related preclinical model and/or clinical trial data. We review examples of GPCRs which may offer attractive therapeutic strategies for OA, including receptors for cannabinoids, hormones, prostaglandins, fatty acids, adenosines, chemokines, and discuss the main challenges for developing these therapies.